STUDY OF THE INFLUENCE OF DRYING AGENT TEMPERATURE ON RAW COTTON AND ITS COMPONENTS - ROZMETOV, RAKHMATJON (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The fiber heating temperature was studied during the drying of raw cotton selection S-6524 with a humidity of 10.5% and 15.2% in a 2SB-10 drying drum at temperatures of 100 0C, 150 0C and 200 0C with a capacity of 7 t/hour and 10 t/hour. It was established that the heating temperature of cotton fiber increased after passing raw cotton with a moisture content of 10.5% and 15.2% and a productivity of 7 t/h in a drum dryer at temperatures of 100 0C, 150 0C and 200 0C.